MENINGKATKAN KECERDASAN EMOSIONAL PADA SISWA YANG TINGGAL DI ASRAMA - Winda Anggraini; Mohammad Salehudin; Syatria Adymas Pranajaya (JURNAL PENDIDIKAN ROKANIA, 2021)
The purpose of this study was to find out how to improve the emotional intelligence of students living in dormitories. The method used is a research library or library research. Literature research is carried out by collecting information related to the content of the language through Emotional intelligence, which is the skill in regulating the emotions that exist in individuals. Individuals who have a high level of emotional intelligence can control the level of emotions that exist in them. emotional intelligence cannot be possessed suddenly. The environment has a great influence in shaping emotional intelligence in individuals. The environment has an influence on emotional intelligence, especially parents and teachers. Parents play a role as teachers when children are at home while teachers have a role in increasing students' intelligence at school.